Acute abdominal pain in an adolescent girl with an ovarian yolk sac tumor : A yolk sac tumor in an adolescent girl - Stefanelli, Ettore; Talarico, Valentina; Scavone, Maria; Carboni, Elena; Stranieri, Giuseppe; Galati, Maria Concetta; Salerno, Domenico; Raiola, Giuseppe (Acta Biomedica Atenei Parmensis, 2019)
Yolk sac tumor (YST) is a rare tumor that usually occurs in the first two decades of life. It is considered the second most common malignant germ cell tumor of the ovary, characterized by a rapid growth and a bad prognosis due to the frequent metastasis. We report the case of a 12-year-old girl who came to our observation for an acute abdominal pain. Clinical examination evidenced a vague mass in the suprapubic region and a lower abdomen tenderness, the US imaging revealed a complex lesion of the left ovary (19 x 13 cm) and the alpha-fetoprotein (AFP) resulted high (5858 ng/mL). Computed tomography (CT) revealed a large pelvic mass. The treatment consisted of debulking surgery of yolk sac tumor followed by 4 cycles of BEP protocol (Bleomycin, Etoposide, Cisplatin). After 3 years of follow-up there was no evidence of disease recurrence. (www.actabiomedica.it)